PENERAPAN MODEL PEMBELAJARAN KOOPERATIF BERBANTUAN MEDIA GAMBAR DI KOTA MALANG - Fitri Alfi Husniyah (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2020)
This study aims to determine the efforts of teachers in improving class V Arabic writing skills at MI Hidayatul Mubtadi'in Tasikmadu Malang City. The problem faced is that there are still many students who lack Arabic writing skills because some students do not understand and have not read fluently the letters in Arabic Mufrodat, thus impacting students' writing skills that are not in accordance with the completeness of skills write Arabic. Sources of data were obtained from Arabic class V teacher and class V students totaling 28 children, this study used a qualitative approach with the type of research used was classroom action research, where data obtained based on the results of interviews, observations, and documentation analyzed with data reduction, data presentation and verification or conclusions.The results of this study indicate that teachers use several efforts that have been designed and applied in learning so that efforts can be made to improve students' Arabic writing skills.